Estimating the high risk group for cardiovascular disease in the Norwegian HUNT 2 population according to the 2003 European guidelines: modelling study. Issue 7516 (15th August 2005) - Getz, Linn; Sigurdsson, Johann A; Hetlevik, Irene; Kirkengen, Anna Luise; Romundstad, Solfrid; Holmen, Jostein
Abstract: Objective To estimate the high risk group for cardiovascular disease in a well defined Norwegian population according to European guidelines and the systematic coronary risk evaluation system. Design Modelling study. Setting Nord-Tröndelag health study 1995-7 (HUNT 2), Norway. Participants 5548 participants of the Nord-Tröndelag health study 1995-7, aged 40, 50, 55, 60, and 65. Main outcome measures Distribution of risk categories for cardiovascular disease, with emphasis on the high risk group. Main results At age 40, 22.5% (95% confidence interval 19.3% to 25.7%) of women and 85.9% (83.2% to 88.6%) of men were at high risk of cardiovascular disease. Corresponding numbers at age 50 were 39.5% (35.9% to 43.1%) and 88.7% (86.3% to 91.0%) and at age 65 were 84.0% (80.6% to 87.4%) and 91.6% (88.6% to 94.1%). At age 40, one out of 10 women and no men would be classified at low risk for cardiovascular disease. Conclusion Implementation of the 2003 European guidelines on prevention of cardiovascular disease in clinical practice would classify most adult Norwegians at high risk for fatal cardiovascular disease.